A disposição de homens e mulheres para o perdão - Silva, Eudes Nascimento da (2023)
This study aimed to investigate interpersonal forgiveness of injustices suffered in the contexts of family, work, friendship and romantic partners. We sought to verify whether there are significant differences between men and women in forgiveness and in which context forgiveness occurs significantly. To achieve this objective, quantitative, descriptive and correlational field research was carried out with the participation of 239 people, 34.4% men and 65.6% women aged between 19 and 52 years. Data collection was carried out through of social networks. The questionnaire containing the items was made available to participants through a link shared through digital media. The Interpersonal Conflict Resolution scale was applied, consisting of two subscales: Agreement with Forgiveness to resolve interpersonal problems assessed on a 5-point scale (1 - I do not agree – 5 - I completely agree) and Attitudes towards Forgiveness assessed on a scale out of 5 points (1 - I would not forgive – 5 - I would totally forgive). Both subscales consist of 16 items that describe four events of injustice (lying, physical aggression, humiliation, and broken promise) and four agents of injustice (best friend, romantic partner, relative, and boss). The results showed significant differences between men and women in agreement and attitude towards forgiveness, the analysis of the results showed a significant difference between men and women when the offense was made by the romantic partner, therefore, in the other indicators there were no significant differences in agreement and in the attitude towards forgiveness.